ESTIMATION OF REFERENCE EVAPOTRANSPIRATION FOR COFFEE IRRIGATION MANAGEMENT IN A PRODUCUTIVE REGION OF MINAS GERAIS CERRADO - Fernandes, André Luís Teixeira; Mengua, Rafaella Esthefania Cardoso Gomes; de Melo, Giovani Luiz; de Assis, Leonardo Campos (Coffee Science - ISSN 1984-3909, 2018)
Evapotranspiration (evaporation and transpiration) represents vegetated soil water loss to the atmosphere, can be estimated by various empirical methods. The aim of this study was to evaluate the performance of methods of Blaney-Criddle, Jensen-Haise, Linacre, Solar Radiation, Hargreaves-Samani, Makkink, Thornthwaite, Camargo, Priestley-Taylor and Penman in the estimation of potential evapotranspiration comparing to the standard method Penman-Monteith (FAO56) regarding the climatic conditions of the city of Araxá, MG. A set of 35 years of monthly data (1976 to 2010) was used, working with the climatic elements: temperature, relative humidity, wind speed and insolation. The empirical methods to estimate reference evapotranspiration were compared with the standard method using linear regression, simple statistical analysis, Willmott agreement index (d) and performance index (c). The method of Makkink showed the best performance according to the set of parameters evaluated and it is recommended to calculate ETo in Cerrado of Minas Gerais.